Protective Effect of Lusianthridin on Hemin-Induced Low-Density Lipoprotein Oxidation - Su Wutyi Thant; Noppawan Phumala Morales; Visarut Buranasudja; Boonchoo Sritularak; Rataya Luechapudiporn (MDPI AG, 2021)
Oxidation of low-density lipoprotein (LDL) plays a crucial role in the pathogenesis of atherosclerosis. Hemin (iron (III)-protoporphyrin IX) is a degradation product of hemoglobin that can be found in thalassemia patients. Hemin is a strong oxidant that can cause LDL oxidation and contributes to atherosclerosis in thalassemia patients. Lusianthridin from Dendrobium venustrum is a phenolic compound that possesses antioxidant activity. Hence, lusianthridin could be a promising compound to be used against hemin-induced oxidative stress. The major goal of this study is to evaluate the protective effect of lusianthridin on hemin-induced low-density lipoprotein oxidation (he-oxLDL). Here, various concentrations of lusianthridin (0.25, 0.5, 1, and 2 µM) were preincubated with LDL for 30 min, then 5 µM of hemin was added to initiate the oxidation, and oxidative parameters were measured at various times of incubation (0, 1, 3, 6, 12, 24 h). Lipid peroxidation of LDL was measured by thiobarbituric reactive substance (TBARs) assay and relative electrophoretic mobility (REM). The lipid composition of LDL was analyzed by using reverse-phase HPLC. Foam cell formation with he-oxLDL in RAW 264.7 macrophage cells was detected by Oil Red O staining. The results indicated that lusianthridin could inhibit TBARs formation, decrease REM, decrease oxidized lipid products, as well as preserve the level of cholesteryl arachidonate and cholesteryl linoleate. Moreover, He-oxLDL incubated with lusianthridin for 24 h can reduce the foam cell formation in RAW 264.7 macrophage cells. Taken together, lusianthridin could be a potential agent to be used to prevent atherosclerosis in thalassemia patients.